Analisis dan Performa Disain Tujuh Step Multilevel Inverter - Setiyono setiyono setiyono (Sekolah Tinggi Teknik PLN, 2022)
The Seven Step multilevel inverter has 3 H – Bridge switching circuits which are designed from transistor and IGBT semiconductor circuits. The performance of the switches is regulated by the ignition unit which consists of pulses of frequency with a certain ignition angle. This pulse pulse determines the output voltage form of the H-Bridge multilevel inverter circuit. The output voltage form is a square pulse. There are seven step output voltage levels that are close to a sinusoidal shape, but still contain high levels of harmonics. This large Total Harmonic Distortion (THD) can be overcome by increasing the number of levels or steps in the output voltage by adding an H-Bridge strand to the next level. The modeling of this 7 step multilevel inverter circuit is designed using Matlab Simulink Tools.